Identifying quality gaps in tourism for people with disabilities: Importance-Performance Analysis (IPA) - Skalska, Teresa (Turyzm/Tourism, 2023)
The aim of the article is to assess the significance (importance) and level of inconvenience of selected attributes of tourist services provided at particular stages of the supply chain in tourism (information, accommodation, transport, organization and intermediation) in relation to people with various types and degrees of disability. The survey conducted among the disabled helped to identify quality gaps in the provision of tourism services, taking into account their complementarity and accessibility at every stage of delivery. The method of Importance-Performance Analysis (IPA) and basic measures of descriptive statistics were used to analyze empirical data. The study will help to indicate to what extent the tourist experience of a disabled person and the type of disability affect the assessment of the significance (importance) and inconvenience of selected attributes of tourist services. The results of the research can be used by entrepreneurs to analyze the quality and reliability of services provided by their partners and the behavior and needs of the disabled in tourism. They will also be useful for local and regional authorities responsible for ensuring the competitiveness and inclusiveness of tourism regions.